Urban and Intellectual Beauty: Aspects of Oscar Wilde’s Influence - Wong, Linda (ABEI Journal, 2023)
In the 1920s and 1930s, Chinese scholars exalted Oscar Wilde as a worthy model for others to follow. His ideas about freedom, iconoclasm, and passion without limits tremendously influenced Chinese intellectuals, more so than did his dramatic techniques. This paper examines the literary influence of Salomé on certain Chinese literary works. The Chinese intellectuals of the era understood the fatal physical desires and the meaning and consequence of ultimate defiance in Salomé, but they also saw her invincibility, which in turn was thought to be helpful in achieving breakthroughs in a traditional feudalistic society. In those days, the play was regarded as an unconventional discourse that exemplified a radical personality that was deemed to be suitable for China. The Chinese stories are all set in cities that foreground the individual’s search for assertion and love. Salomé, instead of being a femme fatale, is redefined with a positive and rational attitude that reflects a deeper concern for the role of intellectuals. The transformation is fueled by the desire to affect a change in cultural consciousness in terms of the search for one’s role and the striving for freedom, especially for women. An intellectual and bourgeoisie overtone is apparent in these stories, and it is connected to the underlying urban discourse. The indebtedness to Wilde is more a kind of inspiration than a blind imitation. By studying Salomé’s literary representations in selected Chinese works and by investigating the poetical devices and treatment of certain themes in relation to the sociocultural and intellectual concerns of the Chinese authors, I hope to broaden our understanding on major intellectual concepts in those days.